Electron angular distributions of noble gases in sequential two-photon double ionization. Issue 4 (21st February 2016) - Braune, M.; Hartmann, G.; Ilchen, M.; Knie, A.; Lischke, T.; Reinköster, A.; Meissner, A.; Deinert, S.; Glaser, L.; Al-Dossary, O.; Ehresmann, A.; Kheifets, A.S.; et al.
Abstract : We present an angle resolved study of photoelectrons emitted from ions of the noble gases neon, argon and krypton by means of time-of-flight spectroscopy. The ionic targets are generated in a sequential two-photon process induced by the free-electron laser FLASH. Values of the anisotropy parameters β 2 and β 4 are derived from electron angular distribution measurements in the photon energy range from 38 to 91 eV and compared with recent theoretical calculations.